Antipsychotic Augmentation of Serotonin Reuptake Inhibitors in Treatment-Resistant Obsessive-Compulsive Disorder: An Update Meta-Analysis of Double-Blind, Randomized, Placebo-Controlled Trials - Dold, Markus (Int J Neuropsychopharmacol, 2015)
BACKGROUND: Many patients with obsessive-compulsive disorder do not respond adequately to serotonin reuptake inhibitors. Augmentation with antipsychotic drugs can be beneficial in this regard. However, since new relevant randomized controlled trials evaluating new antipsychotics were conducted, a recalculation of the effect sizes appears necessary. METHODS: We meta-analyzed all double-blind, randomized, placebo-controlled trials comparing augmentation of serotonin reuptake inhibitors with antipsychotics to placebo supplementation in treatment-resistant obsessive-compulsive disorder. The primary outcome was mean change in the Yale-Brown Obsessive–Compulsive Scale total score. Secondary outcomes were obsessions, compulsions, response rates, and attrition rates. The data collection process was conducted independently by 2 authors. Hedges’s g and risks ratios were calculated as effect sizes. In preplanned meta-regressions, subgroup analyses, and sensitivity analyses, we examined the robustness of the results and explored reasons for potential heterogeneity. RESULTS: Altogether, 14 double-blind, randomized, placebo-controlled trials (n=491) investigating quetiapine (N=4, n=142), risperidone (N=4, n=132), aripiprazole (N=2, n=79), olanzapine (N=2, n=70), paliperidone (N=1, n=34), and haloperidol (N=1, n=34) were incorporated. Augmentation with antipsychotics was significantly more efficacious than placebo in Yale-Brown Obsessive–Compulsive Scale total reduction (N=14, n=478; Hedges’s g=-0.64, 95% CI: -0.87 to -0.41; P=<.01). Aripiprazole (Hedges’s g=-1.35), haloperidol (Hedges’s g=-0.82), and risperidone (Hedges’s g=-0.59) significantly outperformed placebo. Antipsychotics were superior to placebo in treating obsessions, compulsions, and achieving response. There was no between-group difference concerning all-cause discontinuation. The nonsignificant meta-regressions suggest no influence of the antipsychotic dose or baseline symptom severity on the meta-analytic results. CONCLUSIONS: According to our findings, antipsychotic augmentation of serotonin reuptake inhibitors can be regarded as an evidence-based measure in treatment-resistant obsessive-compulsive disorder.